PERMBERDAYAAN BANK SAMPAH BERBASIS DIGITAL DALAM UPAYA MENDUKUNG GREEN ACCOUNTING PADA BANK SAMPAH SEMPULUR ASRI GEDAWANG: PERMBERDAYAAN BANK SAMPAH BERBASIS DIGITAL DALAM UPAYA MENDUKUNG GREEN ACCOUNTING PADA BANK SAMPAH SEMPULUR ASRI GEDAWANG - Adhi, Nurseto; Rikawati; Sari, Mella Katrina; Rabinah, Aiun Hayatu (Bangun Rekaprima, 2025)
The establishment of the Sempulur Asri Waste Bank began with the establishment of the Sempulur Asri Waste Bank located in RW 5, Gedawang Village, which was pioneered in 2014. The increase in the number of customers made management overwhelmed the management with the problems experienced, there were three main problems in the form of conventional customer account management, suboptimal marketing of the Sempulur waste bank, and incomplete and conventional production equipment. The solution to the problem of conventional customer account management is to digitize the management of the Sempulur Waste Bank account. Solutions for managers who do not master information technology, training and assistance in digitizing the management of the Sempulur Asri waste bank are absolutely necessary. Solutions for customers who are still unfamiliar with the use of information technology, training and assistance in digitizing for customer accessibility related to mutations. The implementation of empowerment is carried out by creating a system utilizing Google Drive for data and file storage. Then for Google Spreadsheet to recap each customer's account mutations and adding customers. In the implementation, it was later found that it was easy for customers to access the balance. This is because the implementation using email is considered less understandable by the customer. Then checking the account by the customer can use the website. This website is used for free using facilities from google sites